BMKG soft Quality Measurement Using COBIT Framework 5 Case Study: Teluk Bayur Maritime Meteorological Station (Pengukuran Kualitas BMKGsoft Menggunakan Framework COBIT 5 Studi Kasus : Stasiun Meteorologi Maritim Teluk Bayur) - Fajrin Rizaldi; Aggy Gusman; Ulya Mega Wahyuni (Universitas Putra Indonesia YPTK Padang, 2020)
BMKGsoft is a website owned by BMKG that is used to enter certain data obtained. Governance is a structure of relationships and processes to direct and control the organization to achieve its objectives. In thisstudy using the COBIT framework (Control objectives for information and related technologies) version 5, the selected domain in the study was the EDM, APO, DSS, and MEA domains. In the research done overall the average obtained is 2.96 with a maturity scale is on a scale of 3.